Reinterpretation of the Hadith of Tashabbuh: Application of the Double Movement Fazlur Rahman's Theory in Understanding the Hadith - Khikmatiar, Azkiya (Journal of Hadith Studies, 2018)
Double Movement theory initiated by Fazlurrahman is a theory that is basically used to understand the Qur'an. Through this theory Rahman invites interpreters to understand the Qur'an by not releasing the historical context in which the Qur'an is revealed, to then unearthed the general idea so that it can be confronted with the contemporary context. In this paper, the author tries to apply the theory to understand the hadith about tashabbuh. The result of the application of the theory is: the hadith about tashabbuh arises where the number of Muslim community is still limited, so to maintain its existence required identity politics; if confronted with the present reality of the number of Muslims who have spread throughout the world, then the hadith is no longer relevant to be applied literally.